RELATIONSHIP BETWEEN ENTREPRENEURSHIP INTENTION AND TECHNICAL COMPETENCE AMONG ENTREPRENEURS IN RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The intricate interplay between Entrepreneurial Intention (EI) and Technical Competence significantly shapes the entrepreneurial landscape. In the context of River State, Nigeria, where entrepreneurship plays a pivotal role in economic growth, understanding this relationship becomes paramount. This study aimed to investigate EI as a previously unexplored variable that could determine the variance in TC among entrepreneurs. One hundred and eleven entrepreneurs were randomly drawn from different locations in the Port Harcourt metropolis in River State, Nigeria. The participants responded to an open-ended questionnaire. The result showed a significant regression equation F (1,109), = 231.83, P<.05), indicating that EI significantly predicted TC among the cohort with an R2 of 922, demonstrating that EI contributed 9.22% of the variation in TC. In summary, EI and technical competence dance together in the entrepreneurial arena.